Visfatin: New marker of oxidative stress in preterm newborns. (March 2016) - Marseglia, Lucia; D'Angelo, Gabriella; Manti, Marta; Aversa, Salvatore; Fiamingo, Chiara; Arrigo, Teresa; Barberi, Ignazio; Mamì, Carmelo; Gitto, Eloisa
Background: Oxidative stress is involved in several neonatal conditions characterized by an upregulation in the production of oxidative or nitrative free radicals and a concomitant decrease in the availability of antioxidant species. Oxygen, which is obviously vital to survival, can be highly damaging to neonatal tissue which is known to be poorly equipped to neutralize toxic derivatives. Thus, exposure of the newborn infant to high oxygen concentrations during resuscitation at birth increases oxidative damage. Visfatin is an adipocytokine involved in oxidative stress and an important mediator of inflammation that induces dose-dependent production of both pro-inflammatory and anti-inflammatory cytokines. To our knowledge, the diagnostic value of visfatin as a marker of oxidative stress in preterm newborns has not been investigated. Objective: The aim of this study was to evaluate visfatin levels in preterm neonates resuscitated with different concentrations of oxygen in the delivery room. Patients: Fifty-two preterm newborns with gestational age less than 32 weeks, resuscitated randomly with different oxygen concentrations (40%, 60%, or 100%) were enrolled at the University Hospital of Messina, over a 12-month period to evaluate serum visfatin levels at T0 (within 1 h after birth), T24 h, T72 h, and T168 h of life. Results: At T72 h and T168 h, higher serum visfatin values in the high-oxygen group compared to the low- and mild-oxygen subjects ( P = 0.002 and P <0.001, respectively) were noted. Conclusion: The results of this study suggest that visfatin could be a new marker of oxidative stress in preterm newborns.